SYNTHESIS OF ADJUSTABLE MECHANISM OF SEWING MACHINE AND ITS KINEMATIC ANALYSIS USING SOLIDWORKS - KHARZHEVSKYI, VIACHESLAV; MARCHENKO, MAKSYM; TKACHUK, VITALII; BEREZIUK, OLEH (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The paper is dedicated to the task of optimal design of eight-linked linkage mechanism of the chain stitch sewing machine, for which it is necessary to solve the problem of the adjustable stroke of the needle. The algorithm and corresponding formulas for conducting a kinematic study of the specified mechanism are presented in the article that allows conducting the optimization design using different criteria. The results of calculations using kinematic research formulas are already given, that made it possible to determine the optimal limits of the needle stroke. The conducted research also took into account the need for optimal values of pressure angles in the links of structural groups of the mechanism, which ensures that they do not jam during the operation of the mechanism, with optimal values of the efficiency, without the loss of its functionality. To verify the correctness of the results obtained by the analytical method, a computer model of the sewing machine mechanism was created in the computer modeling software SOLIDWORKS and its main kinematic characteristics were determined using the Computer-Aided Engineering system SOLIDWORKS Motion. It enabled to determine the values of displacements of the links of the mechanism, its velocities and accelerations, besides it proves the working capacity of the mechanism.